Assessing the brake particle emissions for sustainable transport: A review. (October 2022) - Wang, Yachao; Yin, Hang; Yang, Zhengjun; Su, Sheng; Hao, Lijun; Tan, Jianwei; Wang, Xin; Niu, Zhihui; Ge, Yunshan
Abstract: Particles emitted during braking account for a significant proportion of transport-related particles. The brake particles are still beyond supervision because no mandatory regulations were introduced to control the brake particle emissions. Many studies have been conducted about the brake particles, but the materials & methods used by these studies vary a lot, thus reducing the result comparability among these studies. This paper reviewed brake particle emissions from four aspects: experimental methods, emission characteristics, influencing factors, and future works. Six experimental methods corresponding to different application scenarios are summarized, and these methods require different modifications, skills, and expenses. Whatever the experimental methods, the sampling method needs careful design to reduce the particle transport loss and to ensure particle sampling efficiency. The reported brake particle emissions could exceed the sixth stage exhaust emission regulation (both EU and China), depending on the test procedures, friction materials, and data processing. The brake particle covers a broad size distribution (from a few nanometers to tens of microns), and more studies are needed about its physicochemical characteristics. The friction materials, system running-in, and friction temperature will significantly affect the brake particle emission characteristics, and these factors should be considered when designing the study procedure. The patterns about gaseous emission and non-brake particle emission need more attention, as these patterns might be helpful to understand the brake particle emission characteristics. Some filter&collection-based brake particle after-treatments have also been invented. Future studies should focus on the homogeneous test procedure, mechanism analysis, after-treatment, and non-airborne wear et al. Highlights: Different brake particle research methods were assessed. Brake particle emission characteristics are summarized and compared. Major factors affecting the brake particle emission are analyzed. Future concerns for brake particle emission are proposed.